The Search for Meaning in Life Through Continuing and/or Transforming the Bond to a Deceased Spouse in Late Life - Vähäkangas, Auli (Pastoral psychology, 2022)
Bereavement is an ongoing process of negotiation and meaning-making in which widows and widowers make sense of the changed nature of their relationship with their deceased spouse. We analyzed the experiences of meaning in life among older widows and widowers (aged 65+) using interpretative phenomenological analysis (IPA; see Smith et al. in Interpretative phenomenological analysis: Theory, method and research, Sage, 2009), with the following question: How do widows and widowers search for meaning through continuing and/or transforming their bond to their deceased spouse? The results demonstrate that some of the widowed persons sought meaning through rituals or various means of after-death communication with their deceased spouses. Other participants transformed the bond, for example, through clearing out their deceased spouse’s belongings or a process of reconciliation. Many continued and transformed the bond simultaneously, which shows that negotiation of the relationship after the death of a spouse is an ongoing process in which both continuity and change are present. The experience of a violation of meaning in life affected the participants’ capacity to continue their bond with their deceased spouse.